Reasons for English Undergraduate Students to Plagiarize - Dwi Puji Septarini; Mohammad Adnan Latief; Suharmanto Suharmanto (Jurnal Pendidikan Humaniora, 2019)
Abstract: Plagiarism is associated with a form of research misconducts that falsify another’s concepts, opinions, or words and recognize it as private property without giving proper citation of the original source. This article is a part of a larger study on English undergraduate students’ attitude toward pla-giarism which emphasize on the main reasons that might appear for doing plagiarism. This study was conducted at universities in Malang. The data comes from English undergraduate students’ question-naires. The result shows that the students present their confusion in determining their attitude toward plagiarism. This confusion were at least associated with two main reasons; external and internal factors. Further, recommendations for universities are provided.Key Words: plagiarism reason, undergraduate students, reasons, universities in MalangAbstrak: Plagiarisme merupakan salah satu bentuk pelanggaran dalam pemalsuan ide atau kata-kata seseorang yang selanjutnya diklaim sebagai hasil karya pribadi tanpa memberikan pengakuan sebagai sumber asli. Artikel ini merupakan penjabaran dari penelitian utama, yaitu sikap mahasiswa jurusan bahasa Inggris terhadap tindakan plagiarism. Penelitian ini berfokus pada alasan utama yang mungkin muncul ketika mahasiswa melakukan plagiarism. Penelitian dilakukan di beberapa universitas di Malang. Data didapatkan dari angket mahasiswa. Hasil menunjukkan bahwa mahasiswa mengalami kebingungan dalam menentukan sikap mereka terhadap kasus plagiarism. Kebingungan ini dikaitkan dengan dua alasan utama, faktor eksternal dan internal. Selanjutkan, peneliti memberikan rekomendasi untuk univer-sitas. Kata kunci: alasan plagiarisme, mahasiswa sarjana, universitas di malang